Set up a definite integral to find the area of an ellipse with axis lengths $a$ and $b$. Use a trigonometric substitution to find a formula for the area. What happens if $a=b$? Does this agree with a Geometry formula for a circle? Explain.

$$\frac {x^2}{a^2} + \frac{y^2}{b^{2}} = 1$$

where $a$ & $b$ are positive constants.

$B$ = Area of the first quadrant of the ellipse.

Total area = $4B$

\begin{align} & y^{2} = \left(\frac{b^{2}}{a^{2}}\right)({a^{2}-x^{2}}) \\ \implies & y = \frac{b}{a}\sqrt{a^{2}-x^{2}} \end{align} Hence, \begin{align} B & = \int_0^a{\frac{b}{a}\sqrt{a^{2}-x^{2}}}\;dx = \frac{b}{a}\int_0^a{\sqrt{a^{2}-x^{2}}}\;dx \end{align}

To remove $\sqrt{\quad}$, make a trig sub.

$$1 - \sin^{2} \Theta = \cos^{2}\Theta$$

$$x = a\,\sin\Theta$$

\begin{align} B & = \frac{b}{a}\int_0^a{\sqrt{a^{2}-a^{2}\sin^{2}\Theta}\;dx} = \frac{b}{a}\int_0^a{\sqrt{a^{2}(\cos^{2}\Theta)}}\;dx\\ & = \frac{b}{a}\int_0^a{\sqrt{a^{2}}\,\sqrt{\cos^{2}\Theta}}\;dx = \frac{b}{a}\int_0^a{a\,\cos\Theta}\;dx \end{align}

\begin{align} \frac{dx}{dΘ} = (a \, \sin\Theta)' \implies dx = a \, \cos \Theta \, d\Theta \end{align} Therefore, \begin{align} B & = \frac{b}{a}\int_0^a{a \, \cos\Theta(a \, \cos \Theta \, d \Theta)} = \frac{a^{2} \, b}{a}\int_0^a{\cos^{2}\Theta}\;d\Theta = (a \, b)\int_0^a{\cos^{2}\Theta}\;d\Theta \end{align}

I am a little lost up until this point and the formula doesn't seem to be going in the direction it needs to so that it will become the area of an ellipse. I feel like I made a mistake somewhere along the way. Any help is much appreciated!


Hint...You just need to change the limits to $0$ and $\frac {\pi}{2}$ and use the identity $\cos^2\theta=\frac 12(1+\cos2\theta)$ and you will be finished


The only mistake you've made so far was that when you substitued $\Theta$ for $x$, you didn't substitute the limits of integration. Since $x$ is going from $0$ to $a$, $\Theta$ has to go from $0$ to $\frac\pi2$. Once you fix that, your answer will indeed come out to the area of an ellipse.


The integral is pretty trivial. Spoiler:

$$\int \sqrt{a^2-t^2}\ dt = \frac{1}{2} \left(t \sqrt{a^2-t^2}+a^2 \tan ^{-1}\left(\frac{t}{\sqrt{a^2-t^2}}\right)\right)$$

This can be obtained by a simple substitution $t = a\sin(z)$, $dt = a\cos(z)\ dz$

Which turns the integral into

$$a^2\int \cos^2(z)\ dz$$

Which is trivial and straightforward.

Remember that $z = \arcsin\left(\frac{t}{a}\right)$

The final result will be thence:

$$\int_0^a \sqrt{a^2-x^2}\ dx = \frac{1}{4} \pi a^2$$

Now, adjust with the constants.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.